2016
DOI: 10.9734/bjmmr/2016/27482
|View full text |Cite
|
Sign up to set email alerts
|

Technological Tools for Observational Evaluation - the Experience with the Software for Functional Evaluation Scale for Duchenne Muscular Dystrophy – A Pilot Study Software for Observational Evaluation

Abstract: Systematic observation is an indispensable tool in clinical neurology evaluation, but data organization and record are extensive and time-consuming, requiring method and training. Reliable scales facilitate this task and technology can be decisive in the implementation of observational data routines. In this study, we aimed to show the experience of a software development to Albuquerque et al.; BJMMR, 16(11): 1-7, 2016; Article no.BJMMR.27482 2 optimize the application of a clinical observational scale. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Previous studies showed inter-and intra-observer reliability of compensatory movements scoring. 5,14,17,20,21 The domain lowering to the ground and rising from the ground showed excellent intra and inter reliability. 17 The maximum score of lowering to the ground is 10 and the maximum score of rising from the ground is 15.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies showed inter-and intra-observer reliability of compensatory movements scoring. 5,14,17,20,21 The domain lowering to the ground and rising from the ground showed excellent intra and inter reliability. 17 The maximum score of lowering to the ground is 10 and the maximum score of rising from the ground is 15.…”
Section: Methodsmentioning
confidence: 92%
“…Reliability involves test-retest, inter-rater and intra-rater measures, internal consistency, and measurement error, that were previously described for FES-DMD. 5,14,17,20,21 Responsiveness, which is approached in the present study, refers to the ability of an outcome measure to detect change over time in the construct to be measured. It refers to the validity of a change score, and it is distinguished from validity in the taxonomy for reasons of clarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The examiner completed an assessment chart about compensatory movements in FES-DMD-DATA. After that, the software automatically provided the total and partial scores and generated a brief report with all scores (Albuquerque, Caromano, Voos, Favero, & Farcic, 2016). The total score was the sum of the scores of all domains of the activity.…”
Section: Methodsmentioning
confidence: 99%